HOUSEHOLD PROTECTION AGAINST DENGUE HEMORRHAGIC FEVER EPIDEMICS IN COASTAL CITY OF MAKASSAR - Halmer Halide (JOURNAL OF COASTAL DEVELOPMENT, 2010)
The skill of two simple models for predicting Dengue Hemorrhagic Fever (DHF) epidemics in a coastal city of Makassar was evaluated. One model uses persistence while the other uses past dengue cases and climate factors to make predictions. It was shown that the skill of the models was not significantly different. The value of the prediction was also investigated when it was used for deciding whether or not to protect a household from epidemics. When the model predicts that a DHF epidemic was forthcoming, a highly effective but low-cost DEET product was applied to the whole family as protection against mosquito bites. It was found that the cost of implementing such model prediction was much cheaper than other options such as: (i) using protection without any forecast and, (ii) neglecting any protection. It was also found that the value of a forecast depends on forecast skill and the cost-to-loss ratio.